2018
DOI: 10.7759/cureus.3744
|View full text |Cite
|
Sign up to set email alerts
|

Indications, Clinical Outcomes, and Survival Rate of Pediatric Penetrating Keratoplasty in Suburban Malaysia: A 10-year Experience

Abstract: PurposeTo describe the demographics, indications, clinical outcomes and survival rate of penetrating keratoplasty in Malaysian children living in a suburban area, and discuss the literature on paediatric penetrating keratoplasty.MethodologyA retrospective review of medical records was performed on children younger than 17 years of age who had undergone penetrating keratoplasty in Hospital Universiti Sains Malaysia from January 2008 to December 2017. We recorded demographic data, presenting visual acuity, indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 18 publications
1
9
0
11
Order By: Relevance
“…[21] Table 3 summarizes published data on indications for pediatric keratoplasty in both developed and developing countries with the present study included. [5,7,8,12,[14][15][16][17][18][19][20][22][23][24][25][26][27][28][29] Keratoconus in our study, similar to the reports from pediatric keratoplasty in countries such as New Zealand, Italy, and Australia, was the most common indication for keratoplasty. [14][15][16] This was in contrast to the reports from the United States, Singapore, Saudi Arabia, Eastern China, Malaysia, and India in which congenital corneal abnormalities and corneal infections were the top causes of keratoplasty in the pediatric age group.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…[21] Table 3 summarizes published data on indications for pediatric keratoplasty in both developed and developing countries with the present study included. [5,7,8,12,[14][15][16][17][18][19][20][22][23][24][25][26][27][28][29] Keratoconus in our study, similar to the reports from pediatric keratoplasty in countries such as New Zealand, Italy, and Australia, was the most common indication for keratoplasty. [14][15][16] This was in contrast to the reports from the United States, Singapore, Saudi Arabia, Eastern China, Malaysia, and India in which congenital corneal abnormalities and corneal infections were the top causes of keratoplasty in the pediatric age group.…”
Section: Discussionsupporting
confidence: 89%
“…PKP, in our survey, was the most common surgical technique for pediatric keratoplasty, similar to the other reports in which PKP was the only or the predominant surgical procedure for pediatric corneal transplantation. [5,7,12,[14][15][16][17][18][19][20] The indications for pediatric keratoplasty differ worldwide depending on the geographic region. For instance, in developed countries, congenital corneal disorders and nontraumatic acquired keratectasias are the leading indications for pediatric keratoplasty, while acquired corneal scars and ulcers of traumatic or infectious etiologies are on the top in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…This often implies rapid graft rejection; the almost instantaneous and ferocious inflammatory response, along with a robust fibrin reaction, often results in significant scarring with subsequent ocular surface irregularity and instability [4]. Despite these difficulties, surgery is the first-line treatment of CCO in order to ensure the patient’s VA [5].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature the outcomes of pediatric PKP surgery are heterogeneous [3, 5]. Previous research showed that 32.6–78.6% of grafts performed for CCO remain clear for >1 year [5]. However, when stratification criteria are applied, for example the underlying disease and the age of the patient, the outcomes are very different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation